Virtual Reality on the World Wide Web: a Survey of Web Sites - Henderson, J. Fred (International Journal of Virtual Reality, 1996)
The author surveyed the World Wide Web using a number of Internet based search engines and VR resource pages to identify more than 11,300 open text sites dealing with virtual reality. This article identifies several hundred of the best devoted to VRML, VR news groups, VR resources, VR projects, VR software, VR hardware, academic and laboratories involved in VR, associations, publications, companies, and government agencies specializing in VR. The URLs are provided in the printed article. The CD-ROM that accompanies the printed journal also provides direct links to the sites when this article is viewed while simultaneously connected to the World Wide Web.